1999
DOI: 10.1021/op9800865
|View full text |Cite
|
Sign up to set email alerts
|

Application of Oxathiazolidine-S-oxide Chemistry to the Large-Scale Single-Step Synthesis of an O-Arylethanolamine

Abstract: Alternative routes to the arylethanolamine subunit of a development drug have been investigated. The selected route, involving O-alkylation of a phenol using N-benzyloxathiazolidine-S-oxide, was developed to give a process used successfully for pilot plant manufacture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To this end, the β-substituted itaconate salt 17 was prepared via a Horner-Wadsworth-Emmons olefination, and it was found that this substrate could be hydrogenated (Scheme 4) using [(S)-BINAP-Ru-(p-cymene)Cl]Cl to give the product 16 in 88% ee Crystallization as the cyclohexylamine salt gave a purity of >98% ee and a 65% overall yield from itaconate 17. This olefination/hydrogenation approach therefore obviates the need for 22) (a beta-3 agonist) 32 entered development in 1991, intended for the treatment of noninsulin dependent diabetes. The medicinal chemistry route to 22 (Scheme 5) presented a number of challenges for scale-up.…”
Section: Removal Of a Potential Explosion Hazardmentioning
confidence: 99%
“…To this end, the β-substituted itaconate salt 17 was prepared via a Horner-Wadsworth-Emmons olefination, and it was found that this substrate could be hydrogenated (Scheme 4) using [(S)-BINAP-Ru-(p-cymene)Cl]Cl to give the product 16 in 88% ee Crystallization as the cyclohexylamine salt gave a purity of >98% ee and a 65% overall yield from itaconate 17. This olefination/hydrogenation approach therefore obviates the need for 22) (a beta-3 agonist) 32 entered development in 1991, intended for the treatment of noninsulin dependent diabetes. The medicinal chemistry route to 22 (Scheme 5) presented a number of challenges for scale-up.…”
Section: Removal Of a Potential Explosion Hazardmentioning
confidence: 99%